Review: Self-management Support Program on Dietary Behaviors in Patients with Type 2 Diabetes Mellitus - Primanda, Yanuar; Kritpracha, Charuwan (Nurse Media Journal of Nursing, 2011)
Background: Dietary behaviors are the cornerstone in diabetes management. Diabetes self-management support program in which patients play an active role to determine their health care is an important strategy to improve dietary behaviors in type 2 diabetes mellitus (T2DM) patients. Its elements which contribute to the successfulness of the program need to be identified.Purpose: To review and identify the elements of self-management support program to improve dietary behaviors in T2DM patients.Method: An integrative review was conducted. Relevant studies published in English language during last 10-year, measured dietary behaviors in T2DM patients, and retrieved from CINAHL and PubMed were included.Results: 13 experimental studies and 3 meta-analysis studies were reviewed. Goal setting and action planning combined with other strategies (brief counseling and problem solving) seemed more effective to improve dietary behaviors. Either trained lay people or clinicians could lead the program although clinician-led programs were common. Contents and materials of the education vary across the studies. The effects on dietary behaviors could be detected in short term duration of program (<6 months). Continuing follow-up was essential element which face-to-face follow-up as the most common strategy. The utilization of technology such as telephone-call and internet based follow-up might provide more benefits for patients.Conclusion: Diabetes self-management support program is effective to improve dietary behaviors in T2DM patients. Further research is needed to test the effectiveness of goal setting strategy and technology utilization for follow-up strategy such telephone call in Indonesian T2DM population.Keywords: self-management, dietary behaviors, type 2 diabetes mellitus